WORKSHOP E-MODULE GEOGRAPHY BASED ON QR CODE ON MGMP GEOGRAPHY IN SURABAYA - Prasetya, Sukma Perdana; Sri Murtini; Fahmi Fahrudi Fadirubun; Lidya Lestari Sitohang; Leli Anggreini; Ayu Nurhania (Universitas Negeri Surabaya, 2024)
This study focuses on teaching students how to use QR Codes to present content in a dynamic, interactive, and hands-on way for both in-class and individual learning. This is a community service project of UNESA Geography education master's program to prepare 40 Geography Teacher Community (MGMP) Surabaya City to create geography e-modules based on QR codes. A Likert scale is used to evaluate the performance of QR-based module products, and the results are examined using NVivo software and percentages. The result showed, Individuals were able to comprehend and apply the outcomes of this activity, allowing 40 individuals to successfully finish the QR-based geography e-module. According to them, including QR-based geography e-modules into the classroom can boost creativity in geography education. Teachers are now become content creators rather than scavengers of internet content, which improves their capacity to create relevant and personalized lesson plans, according to the study's suggestions and implementation. Keywords: E-module, Geography, QR Code, Likert Scale